2016
DOI: 10.1007/s00404-015-3980-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual management of cervical cancer in pregnancy

Abstract: PurposeThe management of cervical cancer in pregnancy persists to be challenging. Therefore, identification of factors that influence the choice of therapeutic management is pivotal for an adequate patient counseling.MethodsWe present a literature review of 26 studies reporting 121 pregnancies affected by cervical cancer. Additionally, we add a retrospective case series of five patients with pregnancy-associated cervical cancer diagnosed and treated in our clinic between 2006 and 2013.ResultsThe literature rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 45 publications
0
31
0
6
Order By: Relevance
“…34 There are more case reports showed that no abnormalities was observed in infant after the administration of cisplatin in women with cervical cancer. [45][46][47][48] Cisplatin therapy seems the most reliable form of chemotherapy, permitting a good outcome for most patients. It is reported that paclitaxel and carboplatin were used in pregnancy after organogenesis without apparent fetal effects, though the evidence was mainly based on case reports.…”
Section: Treatmentmentioning
confidence: 99%
“…34 There are more case reports showed that no abnormalities was observed in infant after the administration of cisplatin in women with cervical cancer. [45][46][47][48] Cisplatin therapy seems the most reliable form of chemotherapy, permitting a good outcome for most patients. It is reported that paclitaxel and carboplatin were used in pregnancy after organogenesis without apparent fetal effects, though the evidence was mainly based on case reports.…”
Section: Treatmentmentioning
confidence: 99%
“… 5–7 Cervical cancer appears in 0.8–1.5 per 10 000 births, with worse survival outcomes when diagnosed post partum. 5 8 Of note, up to 5% of cervical intraepithelial neoplasia I-II may progress to invasive cancer during gestation. 8 Finally, acute leukaemia and lymphomas are present in 1:75 000–1:100 000 and 1:1000–1:6000 pregnancies, respectively.…”
Section: Statisticsmentioning
confidence: 99%
“… 5 8 Of note, up to 5% of cervical intraepithelial neoplasia I-II may progress to invasive cancer during gestation. 8 Finally, acute leukaemia and lymphomas are present in 1:75 000–1:100 000 and 1:1000–1:6000 pregnancies, respectively. 5 9 Hodgkin's lymphoma is the more frequent hematological malignancy occurring during pregnancy; approximately 3% of Hodgkin's lymphomas are pregnancy associated.…”
Section: Statisticsmentioning
confidence: 99%
“…Cervical cancer, comprising both squamous and glandular differentiation, is not only the fourth most frequent malignancy but also the fourth leading cause of cancer-related death in women worldwide [2]. Inflammation as a cofactor in human papillomavirus (HPV) and cervical carcinogenesis is an active area of research.…”
Section: Introductionmentioning
confidence: 99%